1990
DOI: 10.1029/jb095ib07p11197
|View full text |Cite
|
Sign up to set email alerts
|

Changes in shear wave splitting at Anza near the time of the North Palm Springs Earthquake

Abstract: Changes in shear wave splitting are observed at KNW before and after the M = 6 North Palm Springs earthquake of July 8, 1986. KNW is a station of the Anza seismic network monitoring the Anza seismic gap on the San Jacinto fault, southern California. The gradual increase in the delays between the split shear waves over 3 years at KNW, reported by Peacock et al. (1988), ended in June 1986. The further 2 years of observations analyzed here show that the behavior of the delays changed abruptly near the time of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 26 publications
9
127
0
Order By: Relevance
“…The approach of fracture criticality, and the consequent earthquake, could be recognized by monitoring shear-wave splitting as above small earthquakes. Such changes have been observed (with hindsight) by Crampin et al (1990Crampin et al ( , 1991, Booth et al (1990), Liu et al (1997), and Gao et al (1998). More controlled investigations could be made by cross-hole observations between deviated boreholes (Crampin and Zatsepin, 1997b).…”
Section: Applicationsmentioning
confidence: 99%
“…The approach of fracture criticality, and the consequent earthquake, could be recognized by monitoring shear-wave splitting as above small earthquakes. Such changes have been observed (with hindsight) by Crampin et al (1990Crampin et al ( , 1991, Booth et al (1990), Liu et al (1997), and Gao et al (1998). More controlled investigations could be made by cross-hole observations between deviated boreholes (Crampin and Zatsepin, 1997b).…”
Section: Applicationsmentioning
confidence: 99%
“…Crack-re lated anisotropy obviously plays an important role at low effective confining pressure or at high pore fluid pressure and may have a dominant role in the upper crust (e.g. Peacock et al, 1988;Crampin et al, 1990). In the middle to lower crust, LPO is expected to be the major cause of seismic anisotropy.…”
Section: * Corresponding Authormentioning
confidence: 99%
“…For this station LAC, the re sults cannot invalidate the hypothesis of a crustal contribution to the splitting. Peacock et al (1988) and Crampin et al (1990) analysed shear-wave splitting from local events in the Anza seismic gap. Earthquakes take place in the crust at depths down to 17 km.…”
Section: The San Andreas Faultmentioning
confidence: 99%
“…Hudson's analysis [15,16] shows that increasing crack aspect-ratios of fluid-saturated cracks changes the time-delays between split shear-waves in a specific range of azimuths and incidence angles [35]. Interpreting field observations before a large (M s = 6) earthquake, Peacock et al [42][43][44] first suggested that the observed temporal changes of time-delays in a range of stress-oriented directions could be explained by the accumulation of stress before an impending large earthquake enlarging crack aspect-ratios. The effects of stress on aspect-ratios was later confirmed with APE-modelling the evolution of fluid-saturated cracks as in Fig.…”
Section: Static Effectsmentioning
confidence: 99%